Design and Technical Evaluation of Evaporative Cooling for Prolonging Fresh Potato Shelf Life in Tropical Climates - Ireine Adriana Longdong; Dedie Tooy; Juventus Yoel Mochtar; Lady C. Ch. E. Lengkey; Herry F. Pinatik; Denny Saroinsong (Postgraduate, University of Mataram, 2025)
Postharvest damage to potatoes can occur due to plant physiological disorders, such as evaporation (transpiration), respiration (respiration), tubers sprouting, and tubers becoming too ripe. This research aims to design, manufacture, and test an evaporative cooling device using a direct spray method from a fan into a room or box by conducting technical tests about temperature, humidity (RH), signs of potato damage, weight loss, and water content. The test was carried out using an evaporative cooling device (evaporative cooler) for 30 days. This research tested the effectiveness of the evaporative cooling system compared to room outside storage on potato quality for 30 days observationally. The results show that evaporative cooling equipment can prolong the shelf life of fresh potatoes in tropical areas according to physical parameters such as signs of damage to potatoes during storage, water content, and percentage of weight loss. For future development, increasing the fan and cooling pad to medium size is necessary for more effective equipment. An evaporative cooler is a cost-efficient and sustainable method for preserving agricultural produce in rural areas far from urban centers.